Ley de libre determinación moderna y la 'cuarta opción': Ley internacional y de Estados Unidos (2021)
Under International and U.S. Constitutional Law decolonization is achieved solely via independence, full integration, and freely associated independence”. UN Resolutions 1514 and 1541 (1960) and supposed Constitutional constraints are the oft-cited authoritative statements for this widely held, yet false proposition. Res. 2625 (1970) amended Res. 1541 by adding a fourth decolonization route: “The emergence into any other political status freely determined by a people”. This modern self-determination option is explained in detail in the monograph, including its pragmatic, case-by-case non-dogmatic approach.As constitutional law goes, there are already various non-state sovereigns within the Federal Union. Indian tribes are jurisprudentially describes as “distinct, independent political communities” or “dependent sovereigns” The Commonwealths of Puerto Rico and the Northern Mariana Islands, among others, are also examples of federated non-state sovereigns peoples and  jurisdictions with varying degrees of autonomy, that fit the norms espoused in Res. 2625 and its progeny.